Detection of Als Proteins on the Cell Wall of Candida albicans in Murine Tissues - Hoyer, L. L. (American Society for Microbiology, 1999)
A murine model of disseminated candidiasis was utilized to determine whether Candida albicans Als proteins are produced in vivo. The kidneys, spleen, heart, liver, and lungs were collected from mice inoculated with one of three C. albicans strains (SC5314, B311, or WO-1). Immunohistochemical analysis of murine tissues by using a rabbit polyclonal anti-Als serum indicated that Als proteins were produced by each C. albicans cell in the tissues examined. Patterns of staining with the anti-Als serum were similar among the C. albicans strains tested. These data indicated that Als protein production was widespread in disseminated candidiasis and that, despite strain differences in ALS gene expression previously noted in vitro, Als protein production in vivo was similar among C. albicans strains. The extensive production of Als proteins in vivo and their presence on the C. albicans cell wall position these proteins well for a role in host-pathogen interaction.